Determinants of behavioural indicators of potato (Solanum tuberosum) growers in Kannauj district of Uttar Pradesh - VERMA, ASHWANI KUMAR; DOHAREY, R K; DUBEY, S K; SINGH, O P; SINGH, S N (The Indian Journal of Agricultural Sciences, 2022)
The present study was carried out to find out the factors that may affect the behavioural dimensions of potato farmers, viz. their knowledge and adoption level as well as their knowledge-adoption gap about scientific potato cultivation practices in Kannauj district of Uttar Pradesh during 2016–17. Multiple regression and stepwise regression analysis was done with selected independent variables to see the effect of independent variables on the selected indicators. The analysed data showed that at knowledge level out of 18 variables taken for analysis of regression, four variables, viz. housing pattern, occupation, material possession and formal extension contact were highly significant (P